THE EFFECT OF ISOMETRIC EXERCISE ON BLOOD PRESSURE REDUCTION IN HYPERTENSION: A LITERATURE REVIEW - Arista Maisyaroh; Devi Aulia Putri; Achlish Abdillah; Eko Prasetya Widianto (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Hypertension is a major factor contributing to cardiovascular disease, which is the number one cause of death globally. Basic Health Research Indonesian Ministry of Health data for 2018 showed that hypertension in East Java Province increased in 2018 by 36.32. So, the authors want to know the effect of isometrics on reducing blood pressure. Objective: The authors want to know the effect of isometrics on reducing blood pressure. Design: This study design is a systematic review to search and review article from database and the theory underlying this study or guidance in this systematic literature review using PRISMA. Data Sources: Based on the results of the literature search through six databases, such as EBSCO, Springer, MedPub, Elsevier, Science Direct, and National Nursing Journal with keywords: Hypertension, High Blood Pressure, Resting Blood Pressure, Isometric Training, Isometric Exercise. The data was search since June 2020. Review Methods: The method used in the preparation of the Literature review using the PRISMA checklist and PICOS. Secondary data obtained from the journal with a predetermined discussion. Results: Based on 18 articles in the literature review, it can be concluded that the results for the research is Isometric exercises that are performed are very effective in reducing blood pressure. Conclusion: Isometric exercises that are performed are very effective in reducing blood pressure. The exercise is doing in 3-4 weeks with 4x2 minutes of exercise with a rest duration of 3 minutes.